Pengaruh Pembiayaan Mudharabah, Musyarakah Dan Ijarah Terhadap Profitabilitas Bank Muamalat Indonesia - Abdul Haris Romdhoni; Ferlangga El Yozika (Jurnal Ilmiah Ekonomi Islam, 2018)
This study aims to determine the effect of mudharabah, musyarakah and ijarah financing on profitability at Bank Muamalat Indonesia 2010-2017, either partially or simultaneously. The population in this study is Bank Muamalat Indonesia. Sampling is done by purposive sampling with data period 2010-2017 from financial statements of Bank Muamalat Indonesia counted 32 data. The method used in this study is quantitative descriptive with the aim to get a picture of how much the structure of financing and its effect on the profitability of Bank Muamalat Indonesia. Data collection technique is done by documentation method which is done by collecting data through Bank Muamalat Indonesia website. The method of this research used multiple regression.The result of partial significance test (t-test), this research shows that mudharabah financing has no significant effect on profitability of Bank Muamalat Indonesia. While musyarakah financing negatively affects the profitability of Bank Muamalat Indonesia. Ijarah financing have no significant effect on profitability of Bank Muamalat Indonesia. While simultaneous significance test result (F-test) shows that mudharabah, musyarakah and ijarah financing jointly affect the profitability of Bank Muamalat Indonesia.